Class actions as a means of enhancing access to justice in South Africa - Marumo, Tladi (Rhodes University, Faculty of Law, Law, 2016)
21 years into democracy South Africa is marked by starkly contrasting experiences in the lives of its citizens. For some few, theirs remains a society defined by opulence and social, economic and political entitlements that accompany it. For a few beneficiaries, democracy has brought with it remarkable changes which have translated through their lives in economic, political and socialempowerment and wellbeing. Accompanying these changes has been the establishment and importantly, the enhancement of access to modern political and legal democratic and participatoryinstitutions of governance for these citizens. And yet, for the remaining majority of South Africans, their experience is marked by social and economic deprivation, poverty and vulnerability. These latter experiences are attributable to the historical legacy of colonialism and apartheid which continues to present itself in the form of persistent poverty and inequality in a 'new South Africa.' It is within this new South Africa, that this deprivation is further exacerbated by an increasingly unaccountable and unresponsive government 'at war with its citizens.' Service delivery protests, then have become a (if not the) way in which the poor and vulnerable get together as a collective, to try and take on the government in way they know how within their means, on deprivations of housing, electricity, water, sanitation, social assistance, healthcare and education. Finding an alternative legal means, whereby poor and vulnerable people themselves, may address these challenges is in the purpose of this thesis. However, the emphasis is not on addressing the plight of vulnerable groups through dependency from outside help, but on finding a means in which the agency (albeit constrained) of people to address their own concerns is recognised. The work investigates how law can enhance the collective agency of poor people to change their socioeconomic circumstances. In particular I investigate how the class action, a legal device which can enable people to come together collectively as a class in litigation for the enforcement of their rights of access to housing, electricity, water, sanitation, social assistance, healthcare and education, can achieve this. I provide recommendations on legal reform on how best access to courts can be made easier through the removal of barriers for impoverished communities to collectively enforce their socio-economic rights. I position the Regulation of Gatherings Act, a legislation which is aimed at affording legal protection to protest action, as a as accessible gateway into towards class litigation.
Keywords: Uncatalogued